Психологическая помощь семье, имеющей ребенка с диагнозом «ранний детский аутизм» - Маканова, А.Ж.; Григорова, Ю.Б. (My University, 2016)
Relevance of the article is determined by the increased interest of various specialists (psychologists, teachers, doctors, etc.) to the family. The attention of scientists to the family due not only to the professional issues, but the evidence and the existence of significant challenges in the development of this social institution. The special position in this respect take families raising children with infantile autism (RDA), which is characterized by a high level of manifestation of the "problem."
Keywords: early childhood autism; psychological support; psychological support; child and family